2007
DOI: 10.1007/s00134-006-0504-z
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, treatment, and outcome of severe sepsis in ICU-treated adults in Finland: the Finnsepsis study

Abstract: This prospective study found the incidence of ICU-treated severe sepsis in Finland to be 0.38 per 1,000 of the population. The ICU and hospital mortalities were also lower than earlier reported in United States or Australia. Evidence-based sepsis therapies were not used as often as recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
153
8
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(191 citation statements)
references
References 36 publications
26
153
8
4
Order By: Relevance
“…(49.7%) [28], but higher than that reported in the Finnsepsis study (28.3%) [29]. The impact on mortality of nosocomial sepsis versus community-acquired sepsis was similar to the recently published results of Alberti et al [16].…”
Section: Discussionsupporting
confidence: 81%
“…(49.7%) [28], but higher than that reported in the Finnsepsis study (28.3%) [29]. The impact on mortality of nosocomial sepsis versus community-acquired sepsis was similar to the recently published results of Alberti et al [16].…”
Section: Discussionsupporting
confidence: 81%
“…17,18 Although the likelihood of a culture that shows growth of microorganisms increases in proportion to the severity of the infection, blood cultures that show growth are obtained from only around 40% of patients with severe sepsis or septic shock. 17,19 According to previous studies, the use of PCR diagnostic techniques such as SeptiFast could help increase this percentage significantly. 10,11,20,21 In this study, we observed that blood cultures that showed growth were obtained in only 28.6% of the evaluated patients, which is largely consistent with the findings reported for other studies.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta‐analysis of RCTs reported that the survival benefit of anticoagulant therapy was observed only in sepsis patients with DIC, but not in those without DIC 10. Furthermore, although many epidemiological studies for sepsis have been carried out,11, 12, 13, 14, 15 epidemiological data regarding sepsis in Japan is limited 16, 17…”
Section: Introductionmentioning
confidence: 99%